2013
DOI: 10.1063/1.4818670
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex stimulated Raman microscope for spectral imaging through multi-channel lock-in detection

Abstract: We report the development of a multiplex stimulated Raman microscope for spectral imaging through multi-channel lock-in detection with a single light source. A white pump beam is prepared with a piece of photonic crystal fiber (PCF). The system does not require the synchronization of plural light sources or the scanning of their wavelengths, and thus a jitter-free pair of pump and Stokes beams is obtained, and a high degree of temporal synchronization is attained in the spectra. The multi-channel lock-in detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…The detection sensitivity of our tuned amplifier array is better than the reported lock-in amplifier array 19 and the CMOS camera 18 technologies by nearly two orders of magnitude. For single-color SRS microscopy, the detection sensitivity of 50 μM retinol or 5 mM methanol solution was reported by Freudiger et al with 1 minute integration time 3 .…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The detection sensitivity of our tuned amplifier array is better than the reported lock-in amplifier array 19 and the CMOS camera 18 technologies by nearly two orders of magnitude. For single-color SRS microscopy, the detection sensitivity of 50 μM retinol or 5 mM methanol solution was reported by Freudiger et al with 1 minute integration time 3 .…”
Section: Resultsmentioning
confidence: 70%
“…With such a scheme the acquisition of a complete Raman spectrum is difficult. Parallel detection of SRS signals has been demonstrated recently by using a CMOS array 18 or a multi-channel lock-in amplifier 19 , both having a moderate detection sensitivity of 10 −4 d I / I modulation depth. Notably, the maximum modulation frequency of current multi-channel lock-in amplifiers is less than 100 kHz 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Rock et al (81) demonstrated recovery of the SRS spectrum after fast signal acquisition from a complementary metal-oxide-semiconductor (CMOS) array with a 20 ms integration time. The recent development of a multichannel lock-in detection scheme has shown promise for multiplex SRS imaging (82). The invention of a compact resonant amplifier array has enabled multiplex SRS imaging with 32 μs pixel dwell time (83).…”
Section: Instrumentation Of Crs Microscopymentioning
confidence: 99%
“…For multiplex SRS, a photodiode array (62) or complementary metal-oxide semiconductor array (63) is used to collect dispersed SRS signals. The demodulation can be performed by either subtracting the background from the signal or using demodulators such as a multichannel lock-in amplifier (64) or a tuned amplifier array (31). …”
Section: Building a Coherent Raman Microscopementioning
confidence: 99%